A PRELIMINARY STUDY OF VERBAL HUMOR FOUND IN ELLEN DEGENERES SHOW WITH JACKIE CHAN - Erhadianas, Sriwahyuni; Rahma Yanti; Yalmiadi; Shabri, Irsyad (Prologue: Journal on Language and Literature, 2024)
The study focuses on two main topics: the General Theory of Verbal Humor (GTVH) and types of verbal humor. It seeks to analyze the various types of verbal humor, particularly in Ellen DeGeneres's program with Jackie Chan. To achieve this, Shade's theory will be used to explore types of verbal humor, while Attardo's theory will be employed to analyze the Knowledge Resources (KRs) from GTVH, including Script Opposition (SO), Language (LA), Logical Mechanism (LM), Target (TA), Situation (SI), and Narrative Strategy (NS). In addition, the authors utilized Sudaryanto's theory along with qualitative and descriptive approaches to accomplish the study's objectives. The authorss used a qualitative approach that began with data from transcripts and involved data collection, analysis, and interpretation. According to the authors's research, there are 26 various types of verbal humor in Ellen DeGeneres' show with Jackie Chan in episodes 148 and 154. Satire was the most frequent type of verbal humor, occurring six times, followed by jokes, anecdotes, sarcasm, and riddles, which happened three times, and tall tales and wit, which appeared twice. The analysis was done step-by-step following the GTVH's (KRs) order to investigate verbal humor at its core.